Mixed Characteristics of Activated Charcoal Ori Bamboo and Red Ginger as Air Purifier on Food Cabinets - S. Astuti; F. E. K. Rastini; E. Priskasari; D. H. Praswanto (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2021)
Most of the community while preservation of food using refrigeration machines and chemicals, which less attention to hygiene. The storage space made of wood, glass or plastic where are almost airtight except the refrigerators which have poor air circulation and it cause of cross-contamination and also triggers bacteria growth, virus and fungi that cause decay and also disease source. These problems encourage the researchers to make a hygienic food storage space by consider the air circulation which is given an air purifier natural ingredients combinations that absorb pollutants, heavy metals, and anti-microbials. The air purifier ingredients which expected are original bamboo charcoal active, and red ginger. To make the air purifier can work effectively, a certain balanced composition is needed. The research method used is an experimental method where food ingredients are stored in a space where the air circulation is coated with a particle layer of original bamboo charcoal activate and red ginger rhizome with different compositions. The material used are mixture of charcoal and ginger rhizome by making an air purifier derived from activated charcoal from ori bamboo waste at a certain percentage of charcoal maturity. After that the product will be tested in food storage space with tofu for the food sample. In this research, the composition combination of ori bamboo charcoal active with red ginger extract was 4:0, 3:1, 2:2, 1;3, 0:4 where the ori bamboo charcoal active was used with a maturity percentage of 50%, 75%, 100 %. From the results of the research, it was found that the samples stored without using the filter grew with microbes after the second day, the samples that were filtered with the composition of activated charcoal only grew microbes on the third day and there was a change in the shape of the filter, namely the aqueous filter. Samples with a composition of activated charcoal with varying maturity and ginger extract began to grow with microbes after the fourth day. The best filter results using 100% mature activated charcoal with a composition of activated charcoal and ginger extract, which is 2:2. Microbes that can still grow in that composition are Bacillus substilis but in small quantities and no viruses or other microbes are found.